Description of mature males of the histioteuthid cephalopod Histioteuthis atlantica (Hoyle, 1885) (Cephalopoda: Oegopsida) from the South Atlantic Ocean - Lipiński, M. R. (South African Journal of Marine Science, 1993)
Mature males of Histioteuthis atlantica are described. They differ from immature animals mainly in the unique photophore pattern of the distal portion of the mantle, i.e. in the presence of densely set, lensless photophores. These photophores resemble those on H. elongata, but they are smaller and much more dense on male H. atlantica. The occurrence of the photophore pattern in approximately the same dense concentration on the dorsum as well as the ventrum is unique in the family Histioteuthidae.